Use of Innovative Methods in Uzbeki Language Lessons - Melikova Mukhayo Abdurakhmonovna; Khakimova Khurshida Khamizayevna (Zien Journals, 2022)
Innovative activity refers to the creative approach of the teacher to mastering existing forms and tools for improving his profession. It should also be recognized that the classifications of stable, universally acceptable scientific ideas about innovations and innovative methods in education have not yet been fully formed.
Keywords: Innovative methods; information technology; students; didactic game